Word order and information structure in Romeyka - Neocleous, Nicolaos; Sitaridou, Ioanna (Frontiers in Psychology, 2025)
IntroductionThis study examines the organization of information structure in Romeyka, the only surviving variety of Asia Minor Greek still spoken in present-day Anatolia, Turkey. Given its historical isolation from Modern Greek and its prolonged contact with Turkish, Romeyka presents a unique linguistic environment for analyzing the structural roles of [focus] and [topic].MethodsUsing empirical data, we investigate how [focus] and [topic] are realized in Romeyka. We analyze their structural positioning within the left periphery and examine their association with an ex situ realization.ResultsOur findings indicate that [focus] and [topic] function as independent structural notions in Romeyka. Both elements are consistently positioned in the left periphery, suggesting a systematic approach to information structuring distinct from Modern Greek.DiscussionThe observed patterns provide evidence of a reorganization of information structure in Romeyka, likely influenced by its long-term linguistic isolation and contact with Turkish. Comparisons with Pontic Greek highlight both similarities and differences, offering insights into the potential contact-induced changes in Romeyka’s grammar.